Association between School Meal Participation and BMI Z-Scores Before and After the Federal Healthy Hunger-Free Kids Act. (14th June 2022) - Acosta, Maria; Sanchez-Vaznaugh, Emma; Matsuzaki, Mika; Sanchez, Brisa
Abstract: Objectives: Evaluate differences in the association between school meal participation and BMI z-scores before and after the federal Healthy Hunger-Free Kids Act (HHFKA) among Black and Latinx children using nationally representative survey data. Methods: Data from the 2007–2018 National Health and Nutrition Examination Survey waves were used along with linear regression models to examine associations between self-reported participation in school breakfast or lunch (0, vs 1–2, 3 + days per week) and BMI z-scores, among Black and Latinx children ages 5–17 who were eligible for free or reduced-price meals. The models were constructed separately for Black and Latinx children and adjusted for age, sex, nativity, education of the main caregiver and family income. To evaluate whether the associations differed before and after HHFKA, the adjusted models included an interaction between school meal participation (lunch or breakfast) and the survey wave indicating the period after (2015–2018) versus before (2007–2010) the 2010 HHFKA's standards for school meals took effect. Results: We found differential associations between lunch and breakfast participation and BMI z-scores in the period after versus before HHFKA among Black (p < 0.05), but not Latinx children. Among Black children, breakfast participation 1–2 and 3 + days (vs 0 days) was associated with lower BMI z-scores after HHFKA (−0.68 and −0.27 respectively, though significant only among the former). Further, lunch participation between 1–2 days was significantly associated with lower BMI z-scores (−0.64), whereas participation for 3 + days (vs 0 days) was non-significantly related to higher BMI z-scores (0.03). Conclusions: Participation in school breakfast and lunch was generally associated with lower BMI z-scores after HHFKA among Black, but not among Latinx children. Longitudinal research is needed to assess dietary and obesity effects of large-scale school nutrition policies among children with the highest obesity prevalence and children who are more likely to be exposed to these policies. Funding Sources: The National Heart, Lung, and Blood Institute of the National Institutes of Health and The Robert Wood Johnson Foundation.